Auxiliary Piers on Long-Span Specially Shaped Mixed Steel Structure Main Tower Cable-Stayed Bridge: Research on the Impact on the Dynamic Performance - Shanshan Guo; Deyong Cui; Shaokun Ma (Advances in Materials Science and Engineering)
This study investigates the influence of auxiliary piers on the natural frequency, deformation characteristics, displacements of the related parts, and internal forces of a long-span heterogeneous steel-structured main tower cable-stayed bridge. Taking the Guohe Third Bridge in Anhui Province as an example, the software ANSYS was used to establish a three-dimensional finite element model of a cable-stayed bridge, and the dynamic characteristics of a long-span specially shaped hybrid steel structure main tower cable-stayed bridge with auxiliary piers added to single span and double spans were analysed. The results show that when one or three pairs of auxiliary piers are added to a single span, the changes in the natural frequency and deformation characteristics are smaller than those when there are no auxiliary piers. When one or three pairs of auxiliary piers are added to each of the two spans, the natural frequency and deformation characteristics are relatively low. Auxiliary piers induce relatively large changes; the changes with 3 pairs of auxiliary piers for a single span is compared with those with 1 pair for a single span, and 3 pairs and 1 pair of auxiliary piers are added to both spans for comparison. The natural vibration frequency and deformation characteristics exhibit relatively small changes; the presence or absence of auxiliary piers and the number of auxiliary piers have a greater influence on the vertical displacement of the main girder and less influence on the vertical displacement of the main tower. An appropriate number of auxiliary piers are beneficial to the seismic resistance of a cable-stayed bridge, and if the number of auxiliary piers is too large, the seismic capacity of the bridge is reduced; it is recommended that a pair of auxiliary piers be added to both spans to optimize the overall dynamic performance of a cable-stayed bridge. This research method can be used on similar cable-stayed bridges to optimize their dynamic characteristics by setting a certain number of auxiliary piers.